PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING BERBANTUAN MEDIA PAPAN PINTAR PENCERNAAN TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS V SDN 02 GUNUNG SARIK - Ayu Junia Sari; Trinda Farhan Satria; Ismira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the science learning results of students, many of whom are still below the KKTP. The aim of this research is to determine the significant influence of the application of the Discovery Learning learning model assisted by Digestion Smart Board media on the learning outcomes of class V science and science students at SDN 02 GunungSarik. The type of research is Quasi-experimental design, using the Nonequivalent Posttest-Only Control Group Design research design. The research population was all class V students at SDN 02 GunungSarik. The samples used were class VB (Experiment) and class VA (Control). The sampling technique uses saturated sampling. The data collection technique is to use tests, with the research instrument used in the form of objective test questions in the form of multiple choices. Hypothesis testing uses the t test statistic which is preceded by normality and homogeneity tests at a significance level of 0.05. The posttest results showed that the average score for the experimental class (83.75) was higher than the control class (77.29). The results of the hypothesis test show tcount = 2,697 and ttable = 1,679 so tcount > ttable, then H0 is rejected and H₁ is accepted. The conclusion of this research is that there is a significant influence of the application of the Discovery Learning learning model assisted by Digestion Smart Board Media on the Learning Outcomes of Class V Students at SDN 02 GunungSarik.